15.6k views
1 vote
Help please !!!
If f(x)=3x-1 and g(x) = x + 2 , find ( f +g ) (x)

Help please !!! If f(x)=3x-1 and g(x) = x + 2 , find ( f +g ) (x)-example-1

1 Answer

2 votes

For this case we have the following functions:


f (x) = 3x-1\\g (x) = x + 2

We must find
(f + g) (x). By definition we have to:


(f + g) (x) = f (x) + g (x)

So:


(f + g) (x) = 3x-1 + (x + 2)\\(f + g) (x) = 3x-1 + x + 2

We add similar terms:


(f + g) (x) = 4x + 1

Answer:


(f + g) (x) = 4x + 1

Option D

User Steven Siew
by
5.4k points